Mulk Raj Anand : Coolie : an assessment - Cowasjee, Saros (Oxford University Press, 1976)
Critique of the revised Bodley Head edition of Coolie, a novel, by the Indo-Anglian novelist Mulk Raj Anand, b. 1905.